Trends and distribution of Vibrio cholerae isolates at the National Microbiology Reference Laboratory, Ministry of Health, Uganda, 2014 –2023 - Baliruno, Leah Naluwagga; Namusoosa, Rita; Gidudu, Samuel; Okello, Paul Edward; Nakigozi, Harriet; Okiria, Chris; Ssewanyana, Isaac; Nabadda, Suzan; Najjuka, Grace; Ario, Alex Riolexus (Uganda Public Health, 2018)
Background: As per the World Health Organization, countries including Uganda are to end cholera by 2030 through prevention and treatment. This achievement can be hindered due to rapid changes in antimicrobial response patterns and serotype among other factors. We described confirmed cholera cases by person, place, time, serotype, antimicrobial resistance, and multi-antimicrobial-resistant phenotype patterns, Uganda, 2014–2023. Methods: We conducted a descriptive study using the 2014 – 2023 data on confirmed cholera cases abstracted from the National Microbiology Reference Laboratory (NMRL) register. We described the cases by age group, sex, district, serotype, reporting period, antimicrobial resistance (resistant and intermediate)(rates), and multi-antimicrobialresistant phenotype patterns. We described the confirmed cases and the antimicrobial resistance patterns over time. Mann-Kendall tests for trends were used to test the significance of AMR trends. Results: We identified 489 confirmed cholera cases between January 2014 to December 2023 whose V. cholerae isolates were referred by 35 districts in Uganda. The majority of the identified confirmed cholera cases were male (239, 49%), aged 21- 40 years (170, 38%), had V. cholerae 01 Ogawa (256, 52%) and were from Kampala District (138, 28%). We observed a gradual decline in confirmed cholera cases over time with peaks in 2015, 2018 and 2023. Vibro cholerae 01 ogawa was observed to dominate throughout the period. We observed consistent resistance by V. cholerae to 6 antimicrobials from 2014 to 2023. 194 (39.7%) isolates showed multiple antimicrobialresistant with 90 (18.6%) resistant to more than one class of antimicrobials. Conclusion: We observed males, persons aged 21-40 years, and Kampala District as being most affected with cholera in Uganda with peaks in 2015, 2018, and 2023 and Vibro cholerae 01 Ogawa as the predominate serotype. Consistent antimicrobial resistance was exhibited over time between 2014 and 2023. Intensifying cholera disease prevention by the Ministry of Health targeting males, persons aged 21-40 years, and Kampala District is critical. Routine antimicrobial surveillance to guide informed antimicrobial use and prevent the spread of AMR, especially during cholera outbreaks is important.